Presenting Religious Tourism News Through Journalist Communication Model - Supriadi, Supriadi; Yusraini, Yusraini; Maliki, Umar (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2022)
Journalism is considered as the act of collecting, preparing, compiling, changing, and conveying or disseminating news to the general public through certain media channels. As web time appeared, newscasting faced new difficulties. Rushing at a unique pace, different editorial standards, for example, confirmation entered the stage of redefinition. Another test is the emergence of content assertiveness that puts news broadcasting into small but deep spaces such as scientific reporting, job news coverage, entertainment news casting, design news casting, and travel industry news casting. As an industry, the religious travel industry will not be known by the general public and the possibility of explorers assuming it does not blend and advance sufficiently and widely. In addition to using the correspondence techniques and practices shown, religious tourism locations can also be conveyed through news. What is the procedure for writing encouraging news to advance travel industry objections? This diary proposes a travel industry editorial writing model that can deliver compelling writing results through the development of standard 5W 1H recipes (what, who, when, where, why, and how) and generous content changes tailor-made for travel industry outreach reasons for religious tourism.